Abnormal EEG Responses to TMS During the Cortical Silent Period Are Associated With Hand Function in Chronic Stroke. (July 2017) - Gray, Whitney A.; Palmer, Jacqueline A.; Wolf, Steven L.; Borich, Michael R.
Background . Abnormal brain excitability influences recovery after stroke at which time a prolonged transcranial magnetic stimulation (TMS)–induced electromyographic silent period is thought to reflect abnormal inhibitory interneuron excitability. Cortical excitability can be probed directly during the silent period using concurrent electroencephalography (EEG) of TMS-evoked responses. Objective . The primary study objectives were to characterize TMS-evoked cortical potentials (TEPs) using EEG and to investigate associations with persistent hand and arm motor dysfunction in individuals with chronic stroke. Methods . Thirteen participants with chronic stroke-related mild-moderate arm motor impairment and 12 matched controls completed a single TMS-EEG cortical excitability assessment. TEPs recorded from the vertex during cortical silent period (CSP) assessment and while at rest were used to evaluate differences in cortical excitability between stroke and control participants. Associations between TEPs and CSP duration with measures of upper extremity motor behavior were investigated. Results . Significantly increased TEP component peak amplitudes and delayed latencies were observed for stroke participants compared with controls during CSP assessment and while at rest. Delayed early TEP component (P30) peak latencies during CSP assessment were associated with less manual dexterity. CSP duration was prolonged in stroke participants, and correlated with P30 peak latency and paretic arm dysfunction. Conclusions . Abnormal cortical excitability directly measured by early TMS-evoked EEG responses during CSP assessment suggests abnormal cortical inhibition is associated with hand dysfunction in chronic stroke. Further investigation of abnormal cortical inhibition in specific brain networks is necessary to characterize the salient neurophysiologic mechanisms contributing to persistent motor dysfunction after stroke.